Detector de fuga de corrente em isoladores de redes de transmissão e distribuição de energia elétrica - Silva, José Rosenildo Bezerra da (Universidade Federal Rural do Semi-Árido, 2019)
The energy produced centrally in large plants needs to be transported to consumer points using transmission and distribution lines. Constant supervision of the devices that use these networks is essential to ensure their operating conditions, and thus maintain the quality of service. The proposed work seeks to create a device that assists in the identification of leakage of electric current in the insulator chains of these lines, simplifying as maintenance and data supply operations that support further statistical analysis. An experimental research of an applied nature was then carried out, where an electrical scheme and a circuit layout were performed, allowing the construction of an electronic board model with specific characteristics for this application. As a result, after performing laboratory tests, it was found that the device developed in addition to identifying the presence of leakage electric current fault locally, also allows its remote indication, evidence its functionality.
Keywords: Linhas de transmissão; isoladores; fuga de corrente; detecção; ENGENHARIAS::ENGENHARIA ELETRICA